2014
DOI: 10.1056/nejmoa1215246
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin for Chronic Hepatitis E Virus Infection in Transplant Recipients

Abstract: This retrospective, multicenter study showed that ribavirin as monotherapy may be effective in the treatment of chronic HEV infection; a 3-month course seemed to be an appropriate duration of therapy for most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
386
2
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(423 citation statements)
references
References 40 publications
13
386
2
10
Order By: Relevance
“…6 Ribavirin (RBV) monotherapy is the treatment-of-choice for most patients. 7,8 However, treatment failure has been observed, either as a partial response to ribavirin or viral recurrence after therapy cessation, and is possibly linked to dose reductions because of severe anemia in some cases. 7,8 We report on 15 solid-organ-transplant patients with chronic hepatitis E (11 with genotype 3c, 3 genotype 3f and 1 genotype 3e).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Ribavirin (RBV) monotherapy is the treatment-of-choice for most patients. 7,8 However, treatment failure has been observed, either as a partial response to ribavirin or viral recurrence after therapy cessation, and is possibly linked to dose reductions because of severe anemia in some cases. 7,8 We report on 15 solid-organ-transplant patients with chronic hepatitis E (11 with genotype 3c, 3 genotype 3f and 1 genotype 3e).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…7,8 However, treatment failure has been observed, either as a partial response to ribavirin or viral recurrence after therapy cessation, and is possibly linked to dose reductions because of severe anemia in some cases. 7,8 We report on 15 solid-organ-transplant patients with chronic hepatitis E (11 with genotype 3c, 3 genotype 3f and 1 genotype 3e). RBV treatment was successful in all but 2 patients (both genotype 3c) who failed to clear the virus (13%, which is comparable to other studies reporting failure rates of 15-18%).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective, multicenter study showed that ribavirin monotherapy (600 mg daily) for 3 months may be effective in the treatment of chronic HEV infection. 140 …”
Section: Hepatitis E Virusmentioning
confidence: 99%
“…Ribavirin is recognized to achieve virological clearance in 78% of immunosuppressed patients with chronic hepatitis E. 4 The use of ribavirin in acute hepatitis E is less well described and is limited to case reports (Table 1). [5][6][7][8][9] On review of the literature, 9 patients with acute HEV have been treated with ribavirin for median duration of 7 weeks (10 days to 24 weeks) with median time to virological clearance of 4 weeks (3-8 weeks).…”
mentioning
confidence: 99%